An Examination of the Impact of Entrepreneurial Orientation on Organizational Performance - Maria Angela Diva Wadyatenti (Department of Management - Institut Shanti Bhuana, 2023)
ABSTRACT One of the sectors that have been hit hard by the Covid-19 Pandemic is Micro, Small, and Medium Enterprises (MSMEs), which are the drivers of the Indonesian economy but also have a significant impact on the decline in the level of the national economy. A marketing strategy that is very possible to do is the use of technology which is also one of the important factors in MSME business activities. In the New Normal era, it is not only related to competitive advantages, lower costs, and efficiency but also how this social media can improve organizational performance for the sustainability of MSMEs. In addition, entrepreneurial orientation is very necessary for maintaining a business. This study aims to determine the effectiveness of using social media as a marketing strategy for entrepreneurial orientation and sustainability performance, especially in the MSME sector in Indonesia, this research was conducted with a quantitative design. Data collection technique using a self-administered survey by distributing questionnaires The sampling technique used is purposive sampling. The sample in this study was 54 MSME owners. The data analysis method used to test the hypothesis is SEM analysis using the PLS approach. The results of this study show that the use of social media has a significant effect on entrepreneurial orientation and organizational performance.